EVALUATION OF TOTAL BLOOD LOSS AFTER ADMINISTRATION OF TRANEXAIMC ACID IN TOTAL HIP ARTHROPLASTY - Damjanovikj, Dejan; Georgieva, Daniela; Djoleva Tolevska, Roza; Atanasov, Nenad; Majstorov, Venjamin; Saveski, Aleksandar; Shabani, Ilir; Atanasovski, Igor; Piper, MIhail; Petkovikj, Elena; Komnenovikj, Marina; Sofija Zlateska; et al. (MIT University Skopje, 2025)
Total arthroplasty is one of the most frequent procedures in orthopedic surgery, proven to be an effective treatment that significantly improves patients' quality of life. However, it is associated with considerable perioperative blood loss which can lead to suboptimal outcomes and systemic complications. The aim of this study is to assess the total blood loss after the application of tranexamic acid in patients undergoing total hip arthroplasty surgery. A total of 64 patients were included, divided into two groups: a test group where tranexamic acid was administered intravenously and a control group where tranexamic acid was not used. The values for total blood loss and erythrocyte volume loss were statistically significantly lower in the test group. Blood loss in the control group was higher by an average of 482.19 ml. Erythrocyte loss in the control group was higher by an average of 256.28 ml. The use of tranexamic acid as a standard protocol in total hip arthroplasty is a safe and effective method to reduce total blood loss. Ultimately, this results in a reduced need for blood transfusion, a decrease in potential risks and complications associated with it, and the achievement of pharmacoeconomic benefits.
Keywords: total hip arthroplasty; tranexamic acid